Agrarian social movements: The absurdly difficult but not impossible agenda of defeating right‐wing populism and exploring a socialist future. (21st April 2019) - Borras, Saturnino M.
Abstract: Parallels, resemblances, and interconnections between contemporary right‐wing populism and the populism of agrarian movements are examined in this essay. The two are partly linked through their social base in the countryside. This paper explores an agenda for political conversation and research on possible contributions to the twin efforts of splitting the ranks of right‐wing populists while expanding the united front of democratic challengers. The challenge is how to transform the identified interconnections into a left‐wing political project that can erode right‐wing populism. This requires a reclaiming of populism. In exploring this agenda, the paper revisits the ideas and practices of right‐wing populism and agrarian populism and the awkward overlaps and fundamental differences between them. It concludes with a discussion on the challenge of forging a reformulated class‐conscious left‐wing populism as a countercurrent to right‐wing populism, and as a possible political force against capitalism and towards a socialist future.